2007
DOI: 10.1103/physrevb.76.224424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure ofFe1xCoxSiin a magnetic field studied via small-angle polarized neutron diffraction

Abstract: The magnetic structure of Fe 1−x Co x Si single crystals with x = 0.10, 0.15, 0.20, 0.50 has been studied by small angle polarized neutron diffraction and superconducting quantum interference device measurements. Experiments have shown that in zero field the compounds with x = 0.1, 0.15 have a well-defined tendency to order in the one-handed spiral along ͗100͘ axes due to the anisotropic exchange, that, however, decreases with increasing Co concentration x. The magnetic structure of Fe 1−x Co x Si with x = 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 23 publications
7
65
0
Order By: Relevance
“…Cubic iron monogermanide, FeGe, [1] together with the iso-structural MnSi [2] and MnGe [3] as well as the pseudo-binary compounds Fe 1−x Co x Si (0.1 ≤ x ≤ 0.7) [4,5,6,7], Mn 1−y Co y Si (0 ≤ y < 0.9) [5,8], and Mn 1−z Fe z Si (0 ≤ z < 0.13) [8,9] are non-centrosymmetric cubic helimagnets (space group P 2 1 3, B20-type structure) Table 1. Curie temperature T C , spontaneous magnetic moment µs(T → 0), lattice parameter a, helix period L D , and saturation field H D ≡ H c2 (T = 0) for some cubic helimagnets with B 20-type structure (space group P 2 1 3).…”
Section: Introductionmentioning
confidence: 99%
“…Cubic iron monogermanide, FeGe, [1] together with the iso-structural MnSi [2] and MnGe [3] as well as the pseudo-binary compounds Fe 1−x Co x Si (0.1 ≤ x ≤ 0.7) [4,5,6,7], Mn 1−y Co y Si (0 ≤ y < 0.9) [5,8], and Mn 1−z Fe z Si (0 ≤ z < 0.13) [8,9] are non-centrosymmetric cubic helimagnets (space group P 2 1 3, B20-type structure) Table 1. Curie temperature T C , spontaneous magnetic moment µs(T → 0), lattice parameter a, helix period L D , and saturation field H D ≡ H c2 (T = 0) for some cubic helimagnets with B 20-type structure (space group P 2 1 3).…”
Section: Introductionmentioning
confidence: 99%
“…However, the anisotropy of the system decreases with increasing Co concentration for x ≥ 0.2 and results in a distribution of the helix wave vector. This distribution has been shown to be random for high Co concentration (x = 0.5) 10 . On the other hand, ab initio calculations on Fe 1−x Co x Si revealed that such local disorder at concentrations above x > 0.25 is responsible for the decrease of the polarization of the ferromagnetic half-metallic state.…”
Section: Discussionmentioning
confidence: 91%
“…From the crystal structure of FeSi, the EFG principal axis at the iron site is along 111 directions and the asymmetry parameter is zero 35 . At low Co concentration, the iron moments are along 100 directions but become random with increasing Co concentration 10 . Since the four possible 111 directions are all at an angle of arccos(1/ √ 3) to 100 , diagonal EFG terms drop out of the Hamiltonian, but non-diagonal terms do not (see for example Ref.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations